PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) PALU - Suriani, Ni Nyoman (Fakultas Ekonomi Universitas Tadulako, 2018)
The purposes of this research are: (1) to determine the influence of physical evidence, reliability, responsiveness, assurance, and empathy on customers? satisfaction in the Office of State Property and Auction (KPKNL) Palu, (2) to determine the influence of physical evidence on customers? satisfaction in the KPKNL of Palu (3) to determine the influence of reliability on customers? satisfaction in the KPKNL of Palu, (4) to determine the influence of responsiveness on customers? satisfaction in the KPKNL of Palu (5) to determine the influence of assurance on customers? satisfaction in the KPKNL Palu, (6) to determine the influence of empathy on customer satisfaction in the KPKNL Palu. By using associative research approach, this study examines a sample of 39 customers. Data analysis technique used is multiple linear regressions. The results of hypothesis testing can be concluded that: (1) physical evidence, reliability, responsiveness, assurance, and empathy simultaneously have significant influence on customer satisfaction; (2) partially, physical evidence variable, reliability and responsiveness have non- significant influence on customer satisfaction; (3) assurance and empathy partially have significant influence on customer satisfaction.